2016
DOI: 10.1161/hypertensionaha.116.07474
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Hypotension in the ACCORD (Action to Control Cardiovascular Risk in Diabetes) Blood Pressure Trial

Abstract: Orthostatic hypotension (OH) is associated with hypertension and diabetes mellitus. However, in populations with both hypertension and diabetes, its prevalence, the effect of intensive versus standard systolic blood pressure (BP) targets on incident OH, and its prognostic significance are unclear. In 4266 participants in the Action to Control Cardiovascular Risk in Diabetes (ACCORD) BP trial, seated BP was measured 3 times, followed by readings every minute for 3 minutes after standing. Orthostatic BP change, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
106
4
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 27 publications
5
106
4
10
Order By: Relevance
“…Along these lines, in a secondary analysis of the ACCORD, Fleg and colleagues 11 demonstrated that OH was not associated with CVD events. In addition, they showed that treatment of risk factors associated with both OH and CVD (namely, hyperglycemia and hypertension) had no impact on OH 11. In contrast, our study demonstrates prospective, concurrent, and intermediate‐term relationships between OH and both subclinical and clinical CVD outcomes.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Along these lines, in a secondary analysis of the ACCORD, Fleg and colleagues 11 demonstrated that OH was not associated with CVD events. In addition, they showed that treatment of risk factors associated with both OH and CVD (namely, hyperglycemia and hypertension) had no impact on OH 11. In contrast, our study demonstrates prospective, concurrent, and intermediate‐term relationships between OH and both subclinical and clinical CVD outcomes.…”
Section: Discussioncontrasting
confidence: 57%
“…Several prospective studies reported no association between OH and coronary heart disease (CHD)7, 8, 9 or CVD mortality 10. Similarly, a recent secondary study of ACCORD (Action to Control Cardiovascular Risk in Diabetes Blood Pressure Trial), a trial of blood pressure (BP) reduction in a population with diabetes mellitus, found that although OH was associated with death and heart failure (HF), it was not associated with atherosclerotic events 11. In contrast, many studies have shown that OH is associated with CVD events12, 13, 14, 15, 16, 17 and CVD mortality 14, 18…”
mentioning
confidence: 99%
“…However, recent data suggest that symptomatic hypotension makes up <10% of OH and does not have a stronger association with occurrence of cardiovascular event than asymptomatic OH. 34 These limitations could partially explain the relatively weak prevalence of OH of ≈13% compared with other studies. However, this does not question the strength of the association between OH and dementia, which is probably underestimated as a result of these limitations.…”
Section: Limitationsmentioning
confidence: 85%
“…The persons in this trial were a randomized to treatment with antihypertensive drugs to lower the SBP to <120 mmHg or to <140 mmHg. After 1 year, the SBP was 119.3 mmHg with intensive blood pressure control versus 133.5 mmHg with standard antihypertensive drug treatment (9).…”
mentioning
confidence: 97%
“…The Orthostatic Hypotension in Diabetics in the Action to Control Cardiovascular Risk in Diabetes Blood Pressure (ACCORD BP) trial investigated the prevalence, incidence, and prognostic significance of orthostatic hypotension in the ACCORD BP trial (9,10). The participants in this trial were at high risk for having orthostatic hypotension because they had type 2 diabetes, had hypertension, and were treated with antihypertensive drugs.…”
mentioning
confidence: 99%